2021
DOI: 10.1098/rspb.2021.0797
|View full text |Cite
|
Sign up to set email alerts
|

A latitudinal gradient in thermal transgenerational plasticity and a test of theory

Abstract: Transgenerational plasticity (TGP) occurs when phenotypes are shaped by the environment in both the current and preceding generations. Transgenerational responses to rainfall, CO 2 and temperature suggest that TGP may play an important role in how species cope with climate change. However, little is known about how TGP will evolve as climate change continues. Here, we provide a quantitative test of the hypothesis that the predictability of the environment influences the magnitude of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…An experimental study found that manipulated high environmental predictability and autocorrelation drive the evolution of positive transgenerational plasticity in about 130 generations (Rescan et al 2020). Our findings are consistent with these theoretical and experimental studies, but our study is among the first to connect different autocorrelation scenarios with genetically‐based divergence in nature (Munch et al 2021). The findings suggest that high temporal autocorrelation of climatic conditions may contribute to the evolution of high anticipatory transgenerational plasticity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An experimental study found that manipulated high environmental predictability and autocorrelation drive the evolution of positive transgenerational plasticity in about 130 generations (Rescan et al 2020). Our findings are consistent with these theoretical and experimental studies, but our study is among the first to connect different autocorrelation scenarios with genetically‐based divergence in nature (Munch et al 2021). The findings suggest that high temporal autocorrelation of climatic conditions may contribute to the evolution of high anticipatory transgenerational plasticity.…”
Section: Discussionsupporting
confidence: 92%
“…For annual plants, the high predictability between one and the next year indicates the high predictability between parental and offspring generations. We also calculated the decorrelation time (Munch et al 2021) as the number of years ACFs remain positive, measuring the length of periods that the environment remained predictable.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, performing experiments similar to the current study on M. cinxia populations from lower latitudes (e.g. from France, Spain, Morocco; similar to Munch et al 2021), where temporal autocorrelations for temperature are expected to be higher would allow investigating how climatic predictability drives the evolution adaptive TGP.…”
Section: Discussionmentioning
confidence: 92%
“…Future studies using simulated climate change experiments (e.g., Shama et al, 2014) would allow testing such a hypothesis. Moreover, performing experiments similar to the current study on M. cinxia populations from lower latitudes (e.g., from France, Spain, Morocco; similar to Munch et al, 2021), where temporal autocorrelations for temperature are expected to be higher would allow investigating how climatic predictability drives the evolution adaptive TGP.…”
Section: Discussionmentioning
confidence: 92%